2012
DOI: 10.2527/jas.2011-4210
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of L-lysine transport across equine and porcine jejunal and colonic brush border membrane

Abstract: In nonruminant herbivores, microbially derived AA could contribute to whole-body AA homeostasis and thus decrease predicted AA requirements. However, postileal capacity of AA uptake is currently unknown. Therefore, to test the hypothesis that Lys is transported across the large colon mucosal apical membrane with capacity similar to that of the small intestinal mucosa in the pony and pig, we examined Lys transport in vitro using brush border membrane vesicles (BBMV). Mucosa was collected from the distal jejunum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The explanation for the difference from these results and our study in horses is unclear. Woodward et al (2012) reported no differences in L-lysine transporter's Vmax or KM between porcine and equine jejunum and proximal colon, but that ponies had a greater diffusion of protein in brush border membrane vesicles from both sections than pigs. The question remains as to whether these transporters have varying affinity for l-Arg between species.…”
Section: Discussionmentioning
confidence: 91%
“…The explanation for the difference from these results and our study in horses is unclear. Woodward et al (2012) reported no differences in L-lysine transporter's Vmax or KM between porcine and equine jejunum and proximal colon, but that ponies had a greater diffusion of protein in brush border membrane vesicles from both sections than pigs. The question remains as to whether these transporters have varying affinity for l-Arg between species.…”
Section: Discussionmentioning
confidence: 91%
“…Without confirmation of an in vivo study, some in vitro studies showed that Lalanine and cycloleu cine were actively transported through the serosa layer, but active transport of those amino acids through the mucosa layer was not observed in the equine cecum [39,40], pro viding evidence that there may not be substantial uptake of amino acids from the lumen of the large intestine. On the other hand, lysine transporters across the apical membrane in the equine and swine large colon were found to have a greater capacity but less affinity than those in the jejunum, suggesting meaningful hindgut absorption of lysine [41]. However, it is still unclear whether the proteolytic enzymes exist in the hindgut to degrade microbial protein and make it available for absorption.…”
Section: Amino Acid Absorptionmentioning
confidence: 99%